Outcomes of psychiatric genetic counseling in relation to time since diagnosis and symptom onset. Issue 5 (28th April 2022) - Saxton, Sarah; Inglis, Angela; Morris, Emily; Hercher, Laura; Austin, Jehannine
Abstract: To our knowledge, no studies have yet evaluated whether genetic counseling (GC) outcomes are influenced by the timing of the counseling session in relation to the onset or diagnosis of the condition of interest. We conducted an exploratory retrospective chart review using a database from a psychiatric GC (pGC) clinic, to examine the relationship between GC outcomes and time elapsed between: (a) onset of psychiatric symptoms (time since onset, TSO) and/or (b) psychiatric diagnosis (time since diagnosis, TSD), and the pGC session. Linear regression was used to assess the relationship between change in Genetic Counseling Outcome Scale (GCOS) scores from pre‐GC to 1 month post‐GC and TSO and/or TSD. Charts of 271 patients (80% women, mean age = 39.9 years old) seen between 2012 and 2018 were included in the analyses. Mean TSO = 19.6 years (range 0–62 years), and mean TSD = 11.1 years (range 0–43 years). Overall, empowerment increased after GC regardless of TSO/TSD ( p  < 0.0001, d =  1.11). While there was no relationship between GCOS change and TSD, a negative relationship was observed for TSO ( p  = .032) suggesting better outcomes with shorter TSO, although the effect size was very small ( f 2  = 0.019). Post hoc analysis revealed this effect was driven by two diagnoses, depression ( n  = 164, p  = 0.013) and schizoaffective disorder ( n  = 6, p  = 0.042). For the former, the effect size was very small ( f 2  = 0.038) and for the latter, the probability of type 2 error was high. In sum, our data suggest that TSO/TSD plays a negligible role in outcomes of pGC, with patients benefitting from pGC, regardless how long ago symptoms started/diagnosis was made.